Smooth muscle tumor of uncertain malignant potential (STUMP) of Vulva - Yadav, Munjal; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2022)
A 30-years old nulliparous lady presented with apparently recurrent leiomyoma of vulva and past history of repeated resections. She had firm bilobed non-tender vulval lump and underwent partial vulvectomy. Histopathology revealed Smooth muscle tumor of uncertain malignant potential (STUMP). Conclusion: Vulvar leiomyoma is fairly uncommon and can often be misdiagnosed. Surgical excision and histopathological analysis is helpful/ recommended for final diagnosis of Vulvar STUMP.